2006
DOI: 10.1177/1087054705286053
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Functioning in Children With Subtypes of Attention-Deficit/Hyperactivity Disorder

Abstract: These findings suggest that the subtypes represent two distinct disorders and that, unlike ADHD-C, ADHD-I may not be the result of right hemisphere dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
1
12
0
1
Order By: Relevance
“…Some behavioral studies, using the letter cancelation and line bisection tasks, have supported a subtle right hemisphere deficit in ADHD children (Rolfe et al, 2006;Sheppard et al, 1999;Voeller and Heilman, 1988). The right hemisphere, especially the right frontal region, has also been implicated in maintaining motor behavior (Kertesz et al, 1985), which has been shown to be deficient in ADHD children (Voeller et al, 1989;Voeller and Heilman, 1988).…”
mentioning
confidence: 99%
“…Some behavioral studies, using the letter cancelation and line bisection tasks, have supported a subtle right hemisphere deficit in ADHD children (Rolfe et al, 2006;Sheppard et al, 1999;Voeller and Heilman, 1988). The right hemisphere, especially the right frontal region, has also been implicated in maintaining motor behavior (Kertesz et al, 1985), which has been shown to be deficient in ADHD children (Voeller et al, 1989;Voeller and Heilman, 1988).…”
mentioning
confidence: 99%
“…Preliminary signs of executive abilities appear during the first year of life, but show a dramatic advance around the age of 5 years (Berger, Kofman, Livneh, & Henik, 2007;De Luca & Leventer, 2008). The study of lateralization of EF in this age group indicates a right prefrontal advantage (Rolfe, Hausmann, & Waldie, 2006;Rueda, Rothbart, McCandliss, Saccomanno, & Posner, 2005). Studies of response inhibition conducted with healthy children and adolescents show an increase in maturation of right-prefrontal regions with age (Rubia et al, 2001).…”
Section: Attention-network and Their Developmentmentioning
confidence: 66%
“…The influence of handedness on attention can be interpreted in the context of the asymmetry of the neurobiological substrates of attention. The neural processing of attention is known to be asymmetrical (e.g., Rolfe, Hausmann & Waldie, 2006;Schmidt et al, 2008) and left-handers are thought to have less marked hemispheric asymmetries than dextrals (Bishop, 1990;Schmidt, Oliveira, Krahe, & Filgueiras, 2000). In particular, subjects suffering from ADHD were found to show alteration in the normal pattern of asymmetries in the basal ganglia and frontal lobes (Castellanos et al, 2002;Swanson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%